The Development of the Handwoven Souvenir Cloths of Ban Hwan Community in Namkham Sub-District, Mueang District, Si Sa Ket Province - Sriboonruang, Yanisa (Journal of Human and Society, Sisaket Rajabhat University, 2024)
The development of souvenir products made from handwoven fabric by the Ban Wan community, Nam Kham Sub-district, Mueang District, Si Sa Ket Province, aimed to: (1) study the needs for developing souvenir products made from handwoven fabric in the Ban Wan community, (2) design and develop such souvenir products, and (3) examine the costs and returns of these products. A qualitative research method was employed, involving 15 key informants for interviews and 12 participants in focus group discussions. The findings revealed that: (1) the community expressed a desire to develop additional souvenir products from traditional handwoven fabric, transitioning from local sales to creating tourism souvenirs for visitors, thereby contributing to the economic growth of the community. The preferred product was a handwoven fabric umbrella, primarily utilizing handwoven fabric sourced from local weaving groups. (2) The product design emphasized practicality, aesthetics, and durability. (3) The production cost per unit for the handwoven fabric umbrella included: direct materials such as handwoven fabric (35 THB) and umbrella frames (50 THB), direct labor costs (50 THB for production processes), variable manufacturing costs (4.50 THB), and fixed manufacturing costs (0.50 THB), amounting to a total production cost of 140 THB per unit. The profit margin from selling these souvenirs was 84 THB per unit.